Approximate incremental dynamic analysis using the modal pushover analysis procedure. - Han, Sang Whan (Earthquake engineering & structural dynamics.)
Incremental dynamic analysis (IDA)?a procedure developed for accurate estimation of seismic demand and capacity of structures?requires non-linear response history analysis of the structure for an ensemble of ground motions, each scaled to many intensity levels, selected to cover the entire range of structural response?all the way from elastic behaviour to global dynamic instability. Recognizing that IDA of practical structures is computationally extremely demanding, an approximate procedure based on the modal pushover analysis procedure is developed. Presented are the IDA curves and limit state capacities for the SAC-Los Angeles 3-, 9-, and 20-storey buildings computed by the exact and approximate procedures for an ensemble of 20 ground motions. These results demonstrate that the MPA-based approximate procedure reduces the computational effort by a factor of 30 (for the 9-storey building), at the same time providing results to a useful degree of accuracy over the entire range of responses?all the way from elastic behaviour to global dynamic instability?provided a proper hysteretic model is selected for modal SDF systems. The accuracy of the approximate procedure does not deteriorate for 9- and 20-storey buildings, although their dynamics is more complex, involving several ?modes? of vibration. For all three buildings, the accuracy of the MPA-based approximate procedure is also satisfactory for estimating the structural capacities for the limit states of immediate occupancy, collapse prevention, and global dynamic instability.